FSG Outbound Mobility Programме - National Chiao-Tung University (NCTU), Taiwan - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2019)
The faculty is happy to award a travel fund (living expenses) to two of our postgraduate students, Mr Farish Irfal Mohd Saaid (PhD) and Mr Akmal Arsyad Mohd Raffi (MSc). They will be undertaking a research attachment at the Department of Electronic Engineering, National Chiao-Tung University (NCTU), Taiwan for 3 months. Other stipends will be covered by NCTU and Ministry of Science and Technology -(Add On Grant for International Cooperation). The award was presented by Professor Dr Farida Zuraina Mohd Yusof, Dean of Faculty, this morning. Also present during the ceremony, Professor Dr Ilham Adenan, Head of Postgraduate Office (PPS), Associate Professor Dr Tan Winie, the students' supervisor, Professor Dr Rozana Mohd Dahan, Deputy Dean of Research, Alumni and Industrial Lingkages, Puan Umairah Koya, Deputy Registrar, and PPS staffs. We wish both students all the very best in their research project.